Mapping Innovations in Kitabah Learning: A Systematic Review of Arabic Writing Learning Methods - Islamiyah Sulaeman; Aldi Rehardian MS (Al-Jawhar : Journal of Arabic Language, 2025)
The teaching of kitabah (Arabic writing skill) remains one of the most challenging yet pivotal aspects of Arabic language education for non-native learners. Despite the proliferation of diverse instructional methods ranging from traditional to contemporary digital and gamification-based approaches, no comprehensive synthesis has mapped the innovation landscape of kitabah learning methods to date. This systematic review aims to identify, categorize, and analyze instructional methods used in kitabah learning from 2022 to 2026, drawing on 89 empirical and conceptual studies sourced from Scopus, ScienceDirect, and Google Scholar databases. Following the PRISMA protocol, a rigorous screening process reduced an initial pool of 306 records to 26 studies eligible for final synthesis. Findings reveal five dominant method clusters: (1) classical dictation-based methods (imla'), (2) guided and free composition (insya'), (3) cooperative and collaborative learning methods, (4) technology-mediated and digital methods, and (5) multimodal and AI-assisted methods. Results indicate a clear trend toward technology integration, with gamification, mind mapping, project-based learning, and AI tools increasingly supplementing traditional methods. Teacher enthusiasm, learner motivation, and institutional readiness emerge as cross-cutting moderators of effectiveness. The review concludes with a proposed innovation map and recommendations for future research and pedagogical practice.